2013
DOI: 10.1155/2013/607258
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Biofilms in the Pathogenesis of Shiga‐Toxin‐Producing Escherichia coli Infection

Abstract: The present study was designed to determine the relationships among biofilm formation, cellular stress and release of Shiga toxin (Stx) by three different clinical Shiga toxin-producing Escherichia coli (STEC) strains. The biofilm formation was determined using crystal violet stain in tryptic soy broth or thioglycollate medium with the addition of sugars (glucose or mannose) or hydrogen peroxide. The reactive oxygen species (ROSs) were detected by the reduction of nitro blue tetrazolium and reactive nitrogen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…A study using viable but nonculturable O157 STEC cells showed stresses can induce Shigatoxin production by qRT-PCR and Vero-cytotoxicity assay (Liu et al, 2010). Another study showed that stresses could promote Shiga toxin release as well as biofilm formation (Villegas et al, 2013). In our study, stressed STEC had higher cytotoxicity than non-stressed STEC, and the increased release of toxin may also increase their survival under stressed environments.…”
Section: Influence Of Stresses On the Cytotoxicity Of Stec Grown In Gsupporting
confidence: 53%
“…A study using viable but nonculturable O157 STEC cells showed stresses can induce Shigatoxin production by qRT-PCR and Vero-cytotoxicity assay (Liu et al, 2010). Another study showed that stresses could promote Shiga toxin release as well as biofilm formation (Villegas et al, 2013). In our study, stressed STEC had higher cytotoxicity than non-stressed STEC, and the increased release of toxin may also increase their survival under stressed environments.…”
Section: Influence Of Stresses On the Cytotoxicity Of Stec Grown In Gsupporting
confidence: 53%
“…The biofilm-forming ability of STEC has been investigated under different conditions, using different STEC isolates representing different serotypes and origins (6)(7)(8). Biofilm formation by STEC may be regarded as a survival strategy for this bacterium (9)(10)(11)(12). Indeed, bacteria within a biofilm are protected against several stresses, such as a nutrient-limited environment and sanitizers (13).…”
mentioning
confidence: 99%
“…However, one could also combine both the explanations, because there has been a significant decrease in an overall antioxidant protection in planktonic cells during the stationary phase, and a strong reduction in the level of DCF-DA oxidation to its fluorescent form in the stationary phase of biofilm. Several authors have previously proposed a protective mechanisms for biofilm formed by the microorganisms other thanE.coli (Albesa et al 2004;Singer et al 2009;Arce Miranda et al 2011;Villegas et al 2013). The results have shown an interesting relationship -cells of biofilm have a higher resistance to the mediators that produce hydroxyl radical, but in the case of exposure to the superoxide anion, the nature of this relationship is reversed -which means that they are more resistant than the planktonic forms.…”
Section: Resultsmentioning
confidence: 99%